Mitigation of impacts of voltage sag-swell on a wind-turbine generation system - Li, Yao. (2010)
This report intends to present the research results obtained by the author in Final Year Project No. A1018-082: Mitigation of impacts of voltage sag-swell on a wind-turbine generation system. Due to the fact that wind speed is varying all the time, inevitably the power generated by wind turbine cannot be kept stable. To improve power quality, voltage sag/swell in the interconnected system resulted from changing wind speed is studied and series compensation technique is proposed. In this report, a literature review containing basic knowledge on wind power, wind speed distribution, wind-turbine generation system, power quality, and series compensation technique is elaborated first. The related parameters of a wind-turbine generation system to represent voltage sag/swell are developed in the following chapter. Based on this, the voltage sag/swell has been derived in relation to output power of wind turbine. Furthermore, a case study is performed using a statistical approach to obtain the probability distribution of turbine rpm, output power and voltage variation. The impacts of circuit parameters including short-circuit ratio, R/X ratio and power factor on voltage sag/swell have been investigated. Lastly, some recommendations on future research are provided at the end of the report.